2019
DOI: 10.1002/jso.25819
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of decision‐making in preoperative assessment for older adult prostate cancer patients—A qualitative study

Abstract: Background and Objective: Little research exists which investigates the contextual factors and hidden influences that inform surgeons and surgical teams decisionmaking in preoperative assessment when deciding whether to or not to operate on older adult prostate cancer patients living with aging-associated functional declines and illnesses. The aim of this study is to identify and examine the underlying mechanisms that uniquely shape preoperative surgical decision-making strategies concerning older adult prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Frailty assessments recently developed to evaluate fitness to undergo surgery and optimize perioperative outcomes focus on short-term surgical optimization, rather than on evaluating the longer-term role for curative intervention in a patient with comorbidities. ( 20 22 ) A Canadian observational cohort study of >36 000 men undergoing prostatectomy showed substantial variability among observed and predicted 10-year survival, underscoring the uncertainty physicians face: the observed 10-year survival rate was 88.9%, while the life-table predicted survival rate was 83.3% and the rate estimated by Aggregated Diagnosis Groups (ADG) risk-assessment was just 76.0%. ( 23 ) While the high observed 10-year survival rate may imply that surgeons are correctly choosing patients who will benefit from surgery, the discrepancies among LE assessment tools raises concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty assessments recently developed to evaluate fitness to undergo surgery and optimize perioperative outcomes focus on short-term surgical optimization, rather than on evaluating the longer-term role for curative intervention in a patient with comorbidities. ( 20 22 ) A Canadian observational cohort study of >36 000 men undergoing prostatectomy showed substantial variability among observed and predicted 10-year survival, underscoring the uncertainty physicians face: the observed 10-year survival rate was 88.9%, while the life-table predicted survival rate was 83.3% and the rate estimated by Aggregated Diagnosis Groups (ADG) risk-assessment was just 76.0%. ( 23 ) While the high observed 10-year survival rate may imply that surgeons are correctly choosing patients who will benefit from surgery, the discrepancies among LE assessment tools raises concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting Information S1: file 2 provides an overview of the included studies. Half of the studies focused on breast (10/29) [26][27][28][29][30][31][32][33][34][35] or prostate (5/29) [36][37][38][39][40] cancer. Three studies focused on any type of cancer and comorbid dementia (3/29).…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 , 17 , 18 ] Third, the SEER database does not account for comorbidities, and it may be postulated that PLND may not be performed in patients with a less favorable comorbidity profile, and an adjustment for that variable could not be made in the present study. [ 19 , 20 ] Finally, we did not have information on the extent to which urologists relied on the NCCN guidelines at the time of deciding upon PLND in the patients enrolled in the current study. However, these data are not available in any retrospective multi-institutional or population-based study analyzing adherence to guideline recommendations for PCa as well as for other diseases.…”
Section: Discussionmentioning
confidence: 99%